Middle distillate hydrocracking catalyst containing highly nanoporous stabilized y zeolite

The HNPV SY zeolite-based hydrocracking catalyst addresses the issue of low-value naphtha production by enhancing selectivity for heavy middle distillates, achieving higher yields and quality with improved hydrogen efficiency.

JP2025000619AInactive Publication Date: 2025-01-07CHEVRON USA INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024149960
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2014-10-31
Filing Date
2024-08-30
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional SY zeolites used in hydrocracking processes produce low-value naphtha from undesirable secondary hydrocracking of materials within the jet boiling range, necessitating a catalyst with higher selectivity for heavy middle distillate products, particularly diesel.

Method used

A hydrocracking catalyst utilizing a high nanopore volume (HNPV) SY zeolite with enhanced acid site distribution, characterized by a higher amount of pores in the 20 to 50 nm range and an acid site distribution index factor between 0.02 and 0.12, enhances selectivity for the production of heavier middle distillate products in the 700°F boiling range.

Benefits of technology

The HNPV SY-based catalyst produces higher yields and quality of heavy middle distillates, reducing gas and light product formation, and improving hydrogen efficiency compared to conventional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000619000001_ABST
    Figure 2025000619000001_ABST
Patent Text Reader

Abstract

To provide: a hydrocracking catalyst that exhibits a higher degree of selectivity towards production of heavy middle distillate products, particularly diesel products; and a method of hydrocracking hydrocarbonaceous feedstock.SOLUTION: A hydrocracking catalyst comprises: a support; an amorphous silica alumina material; a high nanopore volume stabilized Y zeolite having a nanopore volume in the 20 nm to 50 nm range of 0.15 to 0.6 cc / g; and at least one metal selected from the group consisting of elements from group 6 and groups 8-10 of the periodic table. The high nanopore volume stabilized Y zeolite has an enhanced acid site distribution compared to conventional SY zeolites.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Described herein is an improved hydrocracking catalyst containing a high nanopore volume (HNPV) stabilized Y zeolite (SY), which is further characterized by an enhanced acid site distribution compared to conventional SY zeolites.

[0002] The final hydrocracking catalyst utilizing the HNPV SY zeolite component has been shown to be more efficient at reducing CO2 emissions (e.g., lower value C2O3) compared to conventional SY-based hydrocracking catalysts. 1 ~C 4 gas production), higher hydrogen efficiency, and higher yields (380 to 700°F) and quality of heavy middle distillate products. [Background technology]

[0003] Catalytic hydroprocessing refers to a petroleum refining process in which a carbonaceous feedstock is contacted with hydrogen and a catalyst at higher temperatures and pressures for the purposes of removing undesirable impurities and / or converting the feedstock into improved products.

[0004] Hydrocracking is an important refining process used to produce and process middle distillate products boiling in the range of 250 to 700°F (121 to 371°C), such as kerosene and diesel. Hydrocracking feedstocks contain large amounts of organic sulfur and nitrogen, which must be removed to meet fuel specifications.

[0005] Hydrocrackers have always produced environmentally friendly products, even before the increased environmental regulations on products. No other process can take low-value, high aromatic, high sulfur and high nitrogen feedstocks and produce a full slate of desirable and attractive products, namely LPG, high-quality diesel fuel, hydrogen-rich FCC feed, ethylene cracker feed, and / or high-quality lube unit feed. Modern hydrocracking was commercialized in the early 1960s. These early units converted light feedstocks (from atmospheric crude towers) into high-value, high-demand gasoline products. In addition, the high volumetric gain of hydrocrackers (greater than 20%) added significantly to the refinery bottoms line. Due to these strong attributes, hydrocracker capacity has been steadily increasing over the years.

[0006] Tightening environmental regulations for gasoline and diesel have made hydrocracking the most important process, resulting in ever-increasing global capacity. Most recent basic hydrocrackers were designed to maximize the production of middle distillates from challenging feedstocks such as FCC light cycle oil, heavy vacuum gas oil, and heavy coker gas oil. Like their predecessors, modern hydrocrackers produce valuable, environmentally friendly distillate products, including large amounts of ultra-low sulfur diesel (ULSD), even with increasingly demanding feedstocks. Early generation hydrocrackers were 10,000 barrels per day, but today many new units exceed 100,000 barrels per day.

[0007] The growing demand for middle distillates, the declining market for high sulfur fuel oils, and increasingly stringent environmental regulations have put enormous margin pressure on refineries, especially those with lower Nelson Complexity Index conversion capacity, and even forced many to close. This recent trend has led to grassroots projects for fraction-oriented conversion technologies. Few, if any, refineries have a conversion strategy focused on FCC technology, and many FCC units are operated in less stringent fraction modes or in some cases converted to propylene units. Hydrocracking offers more flexibility in the opportunity to process crude oil, while producing premium grades of clean fuels that improve refinery margins. Thus, in the past decade alone, more than 90 fixed-bed hydrocracking units have been licensed worldwide. Many of the new refineries and refinery-related projects are targeting operating capacities of 400,000 BPSD or more, thereby increasing average hydrocracker capacity beyond traditional single-train capacities of, in many cases, 65,000 to 70,000 BPSD.

[0008] Generally, conventional hydrocracking catalyst extrudates are composed of (1) at least one acidic component, which may be a crystallized aluminosilicate and / or amorphous silica-alumina; (2) a binder material, such as alumina, titania, silica, etc.; and (3) one or more metals selected from Groups 6 and 8 to 10 of the Periodic Table, particularly nickel, cobalt, molybdenum, and tungsten.

[0009] There are two broad classes of reactions that occur in the hydrocracking process. The first class of reactions involves hydrotreating, where impurities such as nitrogen, sulfur, oxygen and metals are removed from the feedstock. The second class of reactions involves hydrocracking, where carbon-carbon bonds are cleaved or hydrocracked in the presence of hydrogen to produce lower boiling products.

[0010] The hydrocracking catalyst is bifunctional, with the hydrogenation / dehydrogenation reaction promoted by a metal component and the hydrocracking reaction promoted by a solid acid component, both reactions requiring the presence of high pressure hydrogen.

[0011] During hydrocracking, carbocations are formed by contacting the feed with a catalyst. The carbocations undergo isomerization and dehydrogenation to form olefins or beta crack to form olefins and new carbocations. These intermediate products undergo hydrogenation to form lower boiling middle distillate products as shown in the table below. [Table 1] Summary of the Invention [Problem to be solved by the invention]

[0012] When conventional SY zeolites are used in hydrocracking processes, low value naphtha is formed from the undesirable secondary hydrocracking of materials in the jet boiling range. Thus, there is currently a need for hydrocracking catalysts that exhibit a higher degree of selectivity towards the production of heavy middle distillate products (380 to 700°F), especially diesel products. [Means for solving the problem]

[0013] The present invention relates to an improved final hydrocracking catalyst containing a high nanopore volume HNPV SY zeolite component, which is also characterized by an enhanced acid site distribution compared to conventional SY zeolites.

[0014] The HNPV SY zeolite component utilized in the catalysts described herein is characterized by a higher amount of pores in the range of 20 to 50 nm compared to conventional SY zeolites, and the HNPV SY also has an enhanced acid site distribution index factor between 0.02 and 0.12.

[0015] By utilizing SY zeolites having a higher nanopore volume in the range of 20 to 50 nm and a higher acid site distribution as described herein below, the final hydrocracking catalyst has been found to exhibit higher selectivity towards the production of heavier middle distillate products in the boiling range of 380 to 700° F. (193 to 371° C.), particularly middle distillates in the diesel boiling range. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a transmission electron microscope (TEM) image of the conventional USY used in the preparation of the conventional hydrocracking catalyst produced in Example 1.

[0017] [Diagram 2] FIG. 2 is a TEM image of the HNPV USY used in the preparation of the specific hydrocracking catalysts produced in the examples.

[0018] [Diagram 3] FIG. 3 is the pore size distribution of the conventional USY and HNPV USY used in the preparation of the hydrocracking catalyst produced in Example 1, as determined by N2 adsorption.

[0019] [Detailed Description of the Invention] <Introduction> "Periodic Table" refers to the IUPAC Periodic Table of the Elements, dated June 22, 2007, and the numbering system for the Groups of the Periodic Table is as set forth in Chemical and Engineering News, Vol. 63(5), p. 27 (1985).

[0020] "Hydrotreating" or "hydroconversion" refers to a process in which a carbonaceous feedstock is contacted with hydrogen and a catalyst at elevated temperatures and pressures for the purpose of removing undesirable impurities and / or converting the feedstock to desirable products. Such processes include, but are not limited to, methanation, water-gas shift reaction, hydrogenation, hydrotreating, hydrodesulfurization, hydrodenitrogenation, hydrodemetallization, hydrodearomatization, hydroisomerization, hydrodewaxing, and hydrocracking, including selective hydrocracking. Depending on the type of hydrotreating and reaction conditions, the products of hydrotreating can exhibit improved physical properties, such as improved viscosity, viscosity index, saturates content, low temperature properties, volatility, and depolarizability.

[0021] "Hydrocracking" refers to processes in which hydrogenation and dehydrogenation involve the cracking / fragmentation of hydrocarbons, e.g., converting heavier hydrocarbons to lighter hydrocarbons, or converting aromatics and / or cycloparaffins (naphthenes) to acyclic branched paraffins.

[0022] "Column" refers to a distillation column or columns that separate a feedstock into one or more fractions having different cut points.

[0023] "Cut point" refers to the temperature on the true boiling point ("TBP") curve (i.e., the batch process curve of the percentage of feed removed in the heavy reflux column versus the temperature reached to achieve that removal) at which a given degree of separation is reached.

[0024] "True boiling point" (TBP) refers to the boiling point of the feed as measured by ASTM D2887-13.

[0025] "Bottoms fraction" means the heavy fraction separated by fractional distillation from the feedstock as the non-vaporized (i.e., bottoms) fraction.

[0026] "Hydrocracking heavy fraction" means the heavy fraction after undergoing hydrocracking.

[0027] "Hydrocarbon" means a compound or substance that contains atoms of hydrogen and carbon, but may include heteroatoms such as oxygen, sulfur or nitrogen.

[0028] "Middle distillates" includes the following products: [Table 2]

[0029] "LHSV" means liquid hourly space velocity.

[0030] "SCF / BBL" (or scf / bbl, or scfb or SCFB) is the amount of gas (N) per barrel of hydrocarbon feed. 2 , H 2 Refers to the standard cubic foot unit for cubic feet (e.g., 12 sq. meters).

[0031] "Nanopore" means a pore having a diameter between 2 nm and 50 nm, inclusive.

[0032] "Stabilized Y zeolite" and "SY" are any Y zeolite that has a higher framework silicon content than the starting (as-synthesized) Na-Y precursor. Exemplary SY zeolites include ultra-stabilized Y (USY) zeolite, very ultra-stabilized Y (VUSY) zeolite, and the like.

[0033] Where permitted, all publications, patents, and patent applications cited in this application are incorporated herein by reference in their entirety to the extent such disclosure is not inconsistent with the present invention.

[0034] Unless otherwise specified, the recitation of a genus of elements, materials or other components, from which individual components or mixtures of components may be selected, is intended to encompass all possible subgenus combinations of the listed components and mixtures thereof. Also, the word "include" and variations thereof are intended to be open-ended, such that the recitation of a listed item does not exclude other similar items that may also be useful in the materials, compositions and methods of the invention.

[0035] Unless otherwise stated, all numerical ranges recited herein are inclusive of the lower and upper limits recited in the range.

[0036] The properties of the materials described herein are measured as follows: (a) Bronsted Acidity: Determined by isopropylamine-temperature-programmed desorption (IPam TPD) adapted from published descriptions in TJ Gricus Kofke, RK Gorte, WEFarneth, J. Catal. 114, 34-45, 1988; TJ Gricus Kifke, RJ Gorte, GT Kokotailo, J. Catal. 115, 265-272, 1989; JG Tittensor, RJ Gorte and DM Happan, J. Catal. 138, 714-720, 1992. (b) SiO 2 / Al 2 O 3 SAR: Determined by ICP elemental analysis. An SAR of infinity (∞) represents the absence of aluminum in the zeolite, i.e., the silica to alumina molar ratio is infinite. In that case, the molecular sieve is composed essentially entirely of silica. (c) Surface area: N at boiling temperature 2 It is determined by adsorption. The BET surface area is P / P 0= 0.050, 0.088, 0.125, 0.163, and 0.200, using a 5-point method. Samples were first dried in dry N 2 The mixture is pretreated at 400° C. for 6 hours in the presence of a stream of (d) Nanopore and micropore volume: N at boiling temperature 2 The micropore volume is determined by adsorption. 0 = 0.050, 0.088, 0.125, 0.163, and 0.200, as calculated by the t-plot method. The samples were first dried in N 2 The mixture is pretreated at 400° C. for 6 hours in the presence of a stream of (e) Nanopore size: N at boiling temperature 2 Mesopore diameters are determined by adsorption of N by the BJH method described in "Determination of pore volume and area distribution in porous materials. I. Computer-aided calculations from nitrogen isotherms" by EP Barrett, LG Joyner, and PP Halenda, J. Am. Chem. Soc., vol. 73, pp. 373-380, 1951. 2 The sample was first dried in N 2 O to remove any adsorbed volatiles such as water or organic matter. 2 It is pretreated in the presence of steam at 400° C. for 6 hours. (f) Total nanopore volume: P / P 0 = 0.990 at boiling temperature 2 The adsorption is determined by the adsorption. The samples are first dried under N 2 2 It is pretreated in the presence of steam at 400° C. for 6 hours. (g) Unit cell size: determined by X-ray powder diffraction. (h) API Gravity: The specific gravity of a petroleum feedstock / product compared to water as determined by ASTM D4052-11. (i) Acid site density: temperature-programmed desorption (TPD) of isopropylamine (IPAm) to quantify the Bronsted acid site distribution of a material is described by Maesen and Hertzenberg in Journal of Catalysis 182, 270-273 (1999). (j) Acid site distribution and index factor: Acid site distribution determined by HD exchange FTIR adapted from the description published by EJM Hensen, DG Poduval, DAJ Michel Ligthart, JA Rob van Veen, and MS Rigutto in J. Phys. Chem. CI, Vol. 114, pp. 8363-8374, 2010. Prior to FTIR measurements, the samples were incubated at 400-450 °C for 1 h with 1 × 10 -5 The sample was then heated under a vacuum of less than 100 Torr. C6D6 was then added to the sample and equilibrated at 80°C. 6 D 6 Spectra were collected in the OH and OD stretching regions before and after addition of . The Brönsted acid site density was determined as the first high frequency OD (HF) at 2676 cm. -1 , the second high frequency OD (HF') is 2653 cm -1 , 2632 cm as the first low frequency OD (LF) -1 and 2620 cm -1 , and the second low frequency OD (LF') at 2600 cm -1 The acid site distribution index (ASDI) factor was determined by using the integrated area of ​​the peaks of HF' + LF' / HF + LF; it represents the content of overactive sites in the zeolite sample.

[0037] <Hydrocracking catalyst composition> The HNPV SY-based hydrocracking catalyst used to hydrocrack the feedstock includes an HNPV SY zeolite, a support component, an amorphous silica alumina (ASA) material, one or more metals, and optionally one or more promoters. The composition of the final HNPV SY catalyst, based on the bulk dry weight of the final HNPV SY catalyst, is set forth in Table 1 below. [Table 3]

[0038] The HNPV SY used to prepare the final HNPV SY-based hydrocracking catalyst described herein has an NPV (20 nm to 50 nm) of 0.15 to 0.6 cc / g and an acid site distribution index (ASDI) factor of between 0.02 and 0.12. In one subembodiment, the HNPV SY has an ADSI of between 0.06 and 0.12. In another subembodiment, the HNPV SY has an ASDI of between 0.08 and 0.11.

[0039] HNPV SY with its unique, enhanced pore size distribution can be produced by conventional methods to introduce zeolitic porosity, including steam treatment, acid / base leaching, and dealumination or desilication by chemical treatment.

[0040] As will be appreciated by those skilled in the art, the manufacturing processes described herein for converting Y zeolite to HNPV SY will vary depending on the characteristics (e.g., particle size, crystal size, alkali content, silica to alumina ratio) of the particular Y zeolite (i.e., the source manufacturer of the zeolite) utilized, the manufacturing equipment installed at the manufacturer's facility over which the manufacturer has typically developed significant body of knowledge regarding its operation and capabilities, and the stage of the manufacturing process at which the HNPV is introduced (e.g., as-made or after ammonium exchange). Thus, based on an understanding of the specific pore size distributions described herein, a manufacturer can then modify the operation of their equipment to convert the stabilized Y zeolite to SY having the specific HNPV described herein.

[0041] Conventionally, as-prepared Y zeolite and SY (Y zeolite dealuminated to produce stable Y zeolite (SY)) can be converted to their HNPV counterparts by hydrothermal treatment using aqueous solutions having a pH between 1 and 6, typically at temperatures between 125 and 900° C., for times as short as 5 minutes to as long as 72 hours. Such treatments typically involve the use of acids (HF, S 2 SO 4 , HNO 3 , AcOH), EDTA or (NH 4 ) 2 SiF 6 and post steam chemical treatment using aqueous solutions containing species such as cellulose acetate, cellulose esters, etc. Additionally, manufacturers use surfactants and pH control agents (e.g., NaOH) to control porosity formation. Pore formation methods are described in the published literature, such as those described in U.S. Patent Application Publication No. 2012 / 0275993 to Olson.

[0042] The ASDI factor is a measure of the concentration of active sites in a zeolite. The distribution of acid sites in a zeolite generally determines the catalytic activity and selectivity for a particular product to be refined. As the concentration of these acid sites increases, during commercial operation the feedstock undergoes more hydrocracking, resulting in the production of less valuable products such as naphtha and less gas production (C 1 ~C 4 ) is increased. It has therefore been found that a reduction in the concentration of these superactive sites (lowering the ASDI factor) results in higher selectivity towards the production of heavier middle distillate products.

[0043] The final hydrocracking catalyst produced using HNPV SY produces less gas and higher yields and quality of heavy middle distillate products compared to conventional hydrocracking catalysts containing conventional SY-based catalysts.

[0044] The HNPV SY zeolites useful in the hydrocracking catalysts described herein are characterized as having the properties set forth in Table 2 below. [Table 4]

[0045] For each embodiment described herein, the HNPV SY hydrocracking catalyst support is selected from the group consisting of alumina, silica, zirconia, titanium oxide, magnesium oxide, thorium oxide, beryllium oxide, alumina-silica, alumina-titanium oxide, alumina-magnesium oxide, silica-magnesium oxide, silica-zirconia, silica-thorium oxide, silica-beryllium oxide, silica-titanium oxide, titanium oxide-zirconia, silica-alumina-zirconia, silica-alumina-thorium oxide, silica-alumina-titanium oxide or silica-alumina-magnesium oxide, preferably alumina, silica-alumina, and combinations thereof.

[0046] The amount of support material in the final hydrocracking catalyst is from 10% to 45% by weight, based on the bulk dry weight of the hydrocracking catalyst. In one subembodiment, the amount of molecular sieve material in the final hydrocracking catalyst is from 15% to 35% by weight.

[0047] The amount of molecular sieve material in the final hydrocracking catalyst is from 0.1 wt.% to 75 wt.% based on the bulk dry weight of the hydrocracking catalyst. In one subembodiment, the amount of molecular sieve material in the final hydrocracking catalyst is from 5 wt.% to 60 wt.%.

[0048] In one embodiment, the HNPV SY zeolite has the properties set forth in Table 3 below. [Table 5]

[0049] In another embodiment, the HNPV SY zeolite has the properties set forth in Table 4 below. [Table 6]

[0050] As described herein above, the final hydrocracking catalyst of the HNPV SY system described herein contains one or more metals. For each embodiment described herein, each metal utilized is selected from the group consisting of elements from Groups 6 and 8 to 10 of the Periodic Table and mixtures thereof. In one subembodiment, each metal is selected from the group consisting of nickel (Ni), cobalt (Co), iron (Fe), chromium (Cr), molybdenum (Mo), tungsten (W) and mixtures thereof. In another subembodiment, the hydrocracking catalyst contains at least one metal from Group 6 and at least one metal selected from Groups 8 to 10 of the Periodic Table. Exemplary metal combinations include Ni / Mo / W, Ni / Mo, Ni / W, Co / Mo, Co / W, Co / W / Mo and Ni / Co / W / Mo.

[0051] The total amount of metal oxide materials in the final hydrocracking catalyst is from 15% to 55% by weight, based on the bulk dry weight of the hydrocracking catalyst. In one subembodiment, the hydrocracking catalyst contains from 3% to 5% by weight nickel oxide and from 15% to 35% by weight tungsten oxide, based on the bulk dry weight of the hydrocracking catalyst.

[0052] The final hydrocracking catalyst described herein may contain one or more promoters selected from the group consisting of phosphorus (P), boron (B), fluorine (F), silicon (Si), aluminum (Al), zinc (Zn), manganese (Mn), and mixtures thereof. The amount of promoter in the hydrocracking catalyst is 0 wt.% to 10 wt.% based on the bulk dry weight of the hydrocracking catalyst. In one subembodiment, the amount of promoter in the hydrocracking catalyst is 1 wt.% to 5 wt.% based on the bulk dry weight of the hydrocracking catalyst.

[0053] <Preparation of Hydrocracking Catalyst> Generally, the hydrocracking catalysts described herein are prepared by the following steps: (a) mixing and peptizing HNPV SY, ASA and a carrier to form an extrudate base; (b) impregnating the base with a metal impregnation solution containing at least one metal; and (c) post-treating the metal-loaded extrudates, which comprises subjecting the extrudates to drying and calcination.

[0054] Prior to impregnation, the extrudate base is dried at a temperature between 90°C and 150°C (194°F and 302°F) for 1 to 12 hours and then calcined at a temperature between 350°C and 700°C (662°F and 1292°F) or higher.

[0055] The impregnation solution is prepared by dissolving the metal precursors in deionized water. The concentration of the solution is determined by the pore volume and metal loading of the support. During a typical impregnation, the support is exposed to the impregnation solution for 0.1 to 10 hours. After an additional 0.1 to 10 hours of immersion, the catalyst is dried at a temperature within the range of 38°C to 149°C (100°F to 300°F) or higher for 0.1 to 10 hours. The catalyst is further calcined in the presence of sufficient air flow at a temperature within the range of 316°C to 649°C (600°F to 1200°F) or higher for 0.1 to 10 hours.

[0056] In one embodiment, the impregnation solution further includes a modifier to promote precipitation of at least one metal. Modifiers and methods of using such modifiers to prepare hydrocracking catalysts are disclosed in U.S. Patent Publication Nos. 20110000824 and 20110132807 to Zhan et al., published on January 6, 2011 and June 9, 2011, respectively.

[0057] <Overview of Hydrocracking> The hydrocracking catalysts described herein are suitable for hydrotreating a variety of hydrocarbonaceous feedstocks including, for example, visbroken gas oils, heavy coker gas oils, gas oils derived from resid hydrocracking or resid desulfurization, other pyrolysis oils, deasphalted oils, Fischer-Tropsch derived feedstocks, cycle oils from FCC units, heavy coal-derived distillates, coal gasification by-product tar, and heavy shale-derived oils, organic waste oils, such as those from pulp / paper mills or waste biomass pyrolysis units, and other disadvantaged feedstocks that would not normally be able to produce middle distillates using conventional one or two stage hydrocracking processes.

[0058] Table 5 below lists typical physical properties of feedstocks suitable for producing middle distillates using the catalysts described herein, and Table 6 lists typical hydrocracking process conditions. [Table 7] [Table 8]

[0059] Prior to introducing the feed to be hydrotreated, the catalyst is heated in a petroleum liquid containing a sulfiding agent at a temperature of 200°F to 800°F (66°C to 482°C) for a period of 1 hour to 7 days under H2O of 100 kPa to 25,000 kPa. 2 The sulfurizing agent is activated by contacting the catalyst under gas pressure. Suitable sulfurizing agents include elemental sulfur, ammonium sulfide, ammonium polysulfide ([(NH 4 ) 2 S] X ), ammonium thiosulfate ((NH 4 ) 2 S 2 O 3 ), Sodium thiosulfate (Na 2 S 2 O 3 ), Thiourea CSN 2 H 4, carbon disulfide, dimethyl disulfide (DMDS), dimethyl sulfide (DMS), dibutyl polysulfide (DBPS), mercaptans, tertiary butyl polysulfide (PSTB), tertiary nonyl polysulfide (PSTN), and ammonium hydrosulfide.

[0060] As discussed above, the final hydrocracking catalyst using the novel HNPV SY component exhibits improved hydrogen efficiency and higher yields and quality of heavy middle distillate products compared to conventional hydrocracking catalysts containing conventional SY.

[0061] Depending on the feedstock, the slate of targeted products and the amount of available hydrogen, the catalysts described herein can be used alone or in combination with other conventional hydrocracking catalysts.

[0062] In one embodiment, the catalyst is disposed in one or more fixed beds in a single stage hydrocracking unit, with or without recycle (once-through). Optionally, the single stage hydrocracking unit may utilize many single stage units operated in parallel.

[0063] In another embodiment, the catalyst is placed in one or more beds and units in a two stage hydrocracking unit, with or without intermediate stage separation and with or without recycle. The two stage hydrocracking unit can be operated using a full conversion configuration, meaning that all of the hydrotreating and hydrocracking is accomplished within the hydrocracking loop with recycle. In this embodiment, one or more distillation units can be utilized within the hydrocracking loop to remove products prior to the second stage hydrocracking step or before recycling the distillation bottoms back to the first and / or second stage.

[0064] The two stage hydrocracking unit can also be operated in a partial conversion configuration, meaning that one or more distillation units are placed within the hydrocracking loop to remove one or more of the incoming streams for further hydroprocessing. Operating the hydrocracking unit in this manner allows the refinery to hydrotreat highly unfavorable feedstocks by allowing undesirable feed components, such as polynuclear aromatics, nitrogen and sulfur species (which deactivate the hydrogenation catalyst), to exit the hydrocracking loop for processing by equipment better suited to handle these components, such as an FCC unit.

[0065] In one embodiment, the two stage hydrocracking configuration is well suited for producing at least one middle distillate and heavy vacuum gas fluidized catalytic cracking feedstock (HVGO FCC), although the catalyst is used in a first stage and optionally a second stage of partial conversion, according to the following steps: (a) hydrocracking a hydrocarbonaceous feedstock to produce a first stage hydrocracking effluent; (b) distilling the hydrocracking feedstock by atmospheric distillation to form at least one middle distillate fraction and an atmospheric bottoms fraction; (c) further distilling the atmospheric bottoms fraction by vacuum distillation to form a side cut vacuum gas oil fraction and a heavy vacuum gas oil FCC feedstock; (d) hydrocracking the side cut vacuum gas oil fraction to form a second stage hydrocracked effluent; and (e) combining said second stage hydrocracking effluent with said first stage hydrocracking effluent.

[0066] The above refinery configuration has several advantages over conventional two stage hydrocracking schemes. First, in this configuration, the first stage catalyst and operating conditions are selected to produce an HVGO FCC stream with only the minimum feed quality required to produce an FCC product that meets established commercial specifications. This is in contrast to conventional two stage hydrocracking schemes, where the first stage hydrocracking unit is operated at the severe conditions necessary to maximize fraction yields, thereby necessitating a unit capable of operating at more severe conditions, which require more hydrogen and shorten catalyst life.

[0067] Second, the sidecut VGO sent to the second stage hydrocracking unit is cleaner and easier to hydrocrack than conventional second stage hydrocracking feeds. Therefore, higher quality middle distillate products can be achieved using a smaller volume of second stage hydrocracking catalyst, which allows smaller hydrocracker reactors to be constructed and consumes less hydrogen. The second stage hydrocracking unit configuration reduces construction costs, catalyst loading costs and operating costs.

[0068] <product> The process of the present invention is particularly useful for producing middle distillate fractions boiling in the range of about 380 to 700° F. (193 to 371° C.). At least 75% by volume, and preferably at least 85% by volume, of the components of the middle distillate have a normal boiling point above 380° F. (193° C.). At least about 75% by volume, and preferably at least 85% by volume, of the components of the middle distillate have a normal boiling point below 700° F. (371° C.).

[0069] Additionally, gasoline or naphtha can be produced by the process of the present invention. Gasoline or naphtha typically boils in the range below 380°F (193°C), but can also be produced in the range below 380°C (193°C). 5 Boils above the boiling point of hydrocarbons, and sometimes 5It may also refer to the boiling range from the boiling point of the hydrocarbon to 400° F. (204° C.). The boiling ranges of the various product fractions recovered at any particular refinery will vary with factors such as the characteristics of the crude oil source, local refinery markets, and product prices.

[0070] The following examples serve to illustrate, but not limit, the present invention. EXAMPLES

[0071] Example 1 <Preparation of Hydrocracking Catalyst> A conventional USY-based hydrocracking catalyst was prepared by the following procedure: 56.4 wt.% USY as described herein, 21 wt.% amorphous silicoaluminate powder (Siral-30 from Sasol), and 22.6 wt.% pseudoboehmite alumina powder (CATAPAL C1 from Sasol) were thoroughly mixed. The mixture was added with diluted HNO 3 An aqueous acid solution (3 wt%) was added to form an extrudable paste. The paste was extruded into a 1 / 16" asymmetric square shape and dried at 248°F (120°C) for 1 hour. The dried extrudates were calcined at 1100°F (593°C) for 1 hour with an excess of dry air purging and cooled to room temperature.

[0072] Impregnation of Ni and W was performed with ammonium metatungstate and nickel nitrate to give 3.8 wt.% NiO and 25.3 wt.% WO based on the bulk dry weight of the final catalyst. 3 The extrudates were then dried at 270° F. (132° C.) for 1 hour. The dried extrudates were then calcined at 950° F. (510° C.) for 1 hour with an excess of dry air purged, and cooled to room temperature.

[0073] A final HNPV USY based hydrocracking catalyst was prepared following the procedure described in Example 1, except that 56.4 wt. % HNPV USY was used instead of the conventional USY.

[0074] The physical properties of the conventional and HNPV USY materials and their acid site distributions after HD exchange are shown in Tables 7 and 8 below.

[0075] Prior to incorporation into the final catalyst, the conventional USY and HNPV USY zeolites were analyzed by transmission electron microscopy (TEM). TEM images of conventional USY and HNPV USY are shown in Figures 1 and 2, respectively.

[0076] In addition, the pore size distributions of the conventional USY and HNPV zeolites were measured, and plots of the pore size distributions of the two zeolites are shown in Figure 3.

[0077] OD acidity was determined by the amount of bridging hydroxyl groups exchanged with deuterated benzene at 80° C., as measured by FT-IR. [Table 9] [Table 10]

[0078] Example 2 <Hydrocracking performance> Conventional USY and HNPV USY catalysts were used to process a typical Middle Eastern VGO. Feed characteristics are shown in Table 11. The experiments were run in a pilot plant unit at 2300 psig total pressure and 1.0 to 2.2 LHSV. The feed passed through a catalyst bed packed with hydrotreating catalyst before entering the hydrocracking zone. Prior to the introduction of the feed, the catalyst was activated with either DMDS (vapor phase sulfiding) or diesel feed with DMDS (liquid phase sulfiding).

[0079] The feed quality and test results are shown below in Tables 9 and 10. As shown in Table 10, the HNPV USY-based catalyst shows improved activity and selectivity to distillate products. The diesel yield increased by 2.6% and the yields to gas and naphtha decreased.

[0080] Furthermore, the HNPV USY-based catalysts reduce the production of undesirable gases and light ends (C 4 - and C 5 -180°F). Additionally, the yield of desirable middle distillates (380 to 700°F) was higher with the HNPV USY-based catalyst than with the conventional USY catalyst. [Table 11] [Table 12]

[0081] Although the present invention has been described in detail with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made therein without departing from the spirit and scope of the invention.

Claims

1. A carrier; an amorphous silica-alumina material; a high nanopore volume stabilized Y zeolite having a nanopore volume of 0.15 to 0.6 cc / g in the range of 20 nm to 50 nm; At least one metal selected from the group consisting of elements of Groups 6 and 8 to 10 of the Periodic Table; A hydrocracking catalyst comprising:

2. 2. The hydrocracking catalyst of claim 1, wherein the high nanopore volume stabilized Y zeolite has an acid site distribution index factor between 0.02 and 0.

12.

3. 3. The hydrocracking catalyst of claim 2, wherein the high nanopore volume stabilized Y zeolite has an acid site distribution index factor between 0.06 and 0.

12.

4. 3. The hydrocracking catalyst of claim 2, wherein the high nanopore volume stabilized Y zeolite has an acid site distribution index factor between 0.08 and 0.

11.

5. 2. The hydrocracking catalyst of claim 1, wherein 20 to 30% of the nanopore volume is in the range of 8 nm to 20 nm.

6. 2. The hydrocracking catalyst of claim 1, wherein 40 to 60% of the nanopore volume is in the range of 20 nm to 50 nm.

7. 2. The hydrocracking catalyst of claim 1, wherein 15 to 25% of the nanopore volume is greater than 50 nm.

8. 1. A process for hydrocracking a hydrocarbonaceous feedstock comprising contacting the hydrocarbonaceous feedstock with a hydrocracking catalyst under hydrocracking conditions to produce a hydrocracked effluent; The hydrocracking catalyst is A carrier; an amorphous silica-alumina material; a high nanopore volume stabilized Y zeolite having a nanopore volume of 0.15 to 0.6 cc / g in the range of 20 nm to 50 nm; At least one metal selected from the group consisting of elements of Groups 6 and 8 to 10 of the Periodic Table; A method comprising:

9. 9. The method of claim 8, wherein the high nanopore volume stabilized Y zeolite has an acid site distribution index factor between 0.02 and 0.

12.

10. 10. The method of claim 9, wherein the high nanopore volume stabilized Y zeolite has an acid site distribution index factor between 0.06 and 0.

12.

11. 10. The method of claim 9, wherein the high nanopore volume stabilized Y zeolite has an acid site distribution index ductor between 0.08 and 0.

11.

12. 9. The method of claim 8, wherein 20 to 30% of the nanopore volume is in the range of 8 nm to 20 nm.

13. 9. The method of claim 8, wherein 40 to 60% of the nanopore volume is in the range of 20 nm to 50 nm.

14. 9. The method of claim 8, wherein 15 to 25% of the nanopore volume is greater than 50 nm.

15. 9. The process of claim 8, wherein the hydrocracked effluent is a heavy middle distillate product in the range of 380 to 700°F (193 to 371°C).

Citation Information

Patent Citations

  • Method for producing zeolite Y having increased mesoporous capacity

    JP1997502416A

  • Hydrogenation decomposition catalyst of hydrocarbon oil and hydrogen decomposition

    JP1999290687A

  • Extremely low-acidity, ultra-stable y-zeolite catalyst compositions and processes

    JP2006505676A

  • Catalyst supports and catalyst compositions, methods for their preparation and methods for their use

    JP2007526119A

  • Hydrocracking catalyst for heavy oil and method for hydrotreating heavy oil using the same

    JP2011031194A